Reading outside the box: exploring critical literacy with Korean preschool children. (4th March 2017) - Kim, So Jung; Cho, Hyesun
ABSTRACT: Despite the increasing attention paid to the importance of critical literacy in North American early childhood classrooms, critical literacy has been rarely discussed in East Asian classrooms, particularly in South Korea. The present study delineates ways in which a Korean preschool teacher interacts with her young learners during literacy activities to foster multiple perspectives on children's literature and challenge dominant ideologies inherent in text. Using qualitative data from participant observations, video and audio recordings, teacher interviews, and children's artifacts, the study provides the detailed examples of how young Korean children negotiated and constructed their voices through critical literacy activities. The teacher used problem-posing and multimodal approaches as ways to open up critical literacy spaces to facilitate the children's critical engagement with books. This study suggests examining how young children interpret text from varied perspectives has great potential for researchers and educators alike as teachers can better support young children in their development of questioning, challenging, and evaluating the meanings and purposes of texts from an early age.